Peningkatan Hasil Belajar dengan Pendekatan Saintifik Menggunakan Blackberry Messenger dan Metode Jigsaw - jaenur, jaenur (Jurnal VARIDIKA, 2016)
This classroom action research is aimed to improve student learning outcomes using a scientific approach with the blackberry messergers  and the jigsaw method.  The application of scientific approaches, media BBM and methods Jigsaw is one of the innovative learning implementation is expected to improve student learning outcomes. Based on the results of the first cycle of the classroom action research showed that: the average attitude score assesment is 76.9, the percentage of mastery of learning outcomes is 61 %.   The average score assessment skills (psychomotor) , project, and portfolio is  77.9, and the percentage of mastery of learning outcomes is 69%. The average of cognitive score (cognitive) on the written test or assignment is 78.0, and the percentage of mastery of learning outcomes is 69%.In the second cycle showed an increase, the average attitude score assesment (attitude) of   XI TIPTL 2 is 81.4, the percentage of mastery of learning outcomes is 89%. The average score assessment skills (psychomotor), project, and portfolio is 82, and the percentage of mastery of learning outcomes is 97%. The average of cognitive score (cognitive) on the written test or assignment is 84.2, and the percentage of mastery of learning outcomes is 97%.